2022
DOI: 10.1021/acsaem.1c03276
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Coupling of Highly Ordered Perovskite Nanocrystals in Supercrystals

Abstract: Assembled perovskite nanocrystals (NCs), known as supercrystals (SCs), can have many exotic optical and electronic properties different from the individual NCs due to energy transfer and electronic coupling in the dense superstructures. We investigate the optical properties and ultrafast carrier dynamics of highly ordered SCs and the dispersed NCs by absorption, photoluminescence (PL), and femtosecond transient absorption (TA) spectroscopy to determine the influence of the assembly on the excitonic properties.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…By comparing results obtained on 9 different NC superlattice samples with the same nominal characteristics, we obtain a value of δ that varies between 40 and 80 meV. The estimated δ allows us to exclude multi-excitons effects, which would cause smaller (10-30 meV) red-shifts in similar systems, [49][50][51][52] and would appear also in disordered NCs. Sample to sample variability manifests also in the fine structure of the ∆R/R signal for ω < 2.37 eV.…”
Section: Cooperative Superradiant Effectsmentioning
confidence: 96%
“…By comparing results obtained on 9 different NC superlattice samples with the same nominal characteristics, we obtain a value of δ that varies between 40 and 80 meV. The estimated δ allows us to exclude multi-excitons effects, which would cause smaller (10-30 meV) red-shifts in similar systems, [49][50][51][52] and would appear also in disordered NCs. Sample to sample variability manifests also in the fine structure of the ∆R/R signal for ω < 2.37 eV.…”
Section: Cooperative Superradiant Effectsmentioning
confidence: 96%
“…A reduction in biexciton binding energy and an increase in carrier cooling rates in superlattices are believed to be responsible for this lower threshold. [131] Another study showed that upon 800 nm excitation, ASE appears in 2D photonic CsPbBr 3 supercrystals at a pump fluence of 10.9 mJ cm −2 , indicating facilitated light coupling between individual nanocrystals. [132] It should be noted that stimulated superfluorescence amplified by modulation of microcavities can also be obtained, which shows quite similar spectral features to ASE.…”
Section: Amplified Spontaneous Emissionmentioning
confidence: 99%
“…2a. [59][60][61][62] First-principle calculation revealed the presence of a confined hole state (CHS), with a size-dependent energetic separation in respect to the valence band (VB) edge states, 63 which explains the dependence of Stokes shift with the NC size. It was verified that the absorption from CHS to the conduction band (CB) is dark (not seen in the UV-Vis absorption spectra) due to the low density of state (DOS).…”
Section: Size-dependent Properties Beyond Bandgapmentioning
confidence: 99%